Defending Interests: Public-Private Partnerships in WTO Litigation - Shaffer, Gregory C. (Rowman & Littlefield Publishers, 2003)
This book examines the growing interaction between private enterprises and public officials to challenge foreign trade barriers. Building on more than one hundred interviews with former and current trade officials and private attorneys in the United States and Europe, Gregory Shaffer calls attention to the ways in which well-organized private parties are using the World Trade Organization's legal system to advance their own commercial ambitions, and how public officials increasingly are dependent on their assistance. Shaffer assesses the historical, political, legal, economic, and cultural factors that have affected the formation of these ad hoc public-private partnerships, as well as trends in the European Union toward U.S.-style practice. He considers the implications of these public-private trade litigation networks for the effectiveness and equity of the WTO system and the stability of U.S.-E.U. relations.